ANALYSIS OF THE INFLUENCE OF CASH HOLDING, QUICK RATIO AND GROWTH OPPORTUNITY ON FIRM VALUE WITH ISLAMIC SOCIAL REPORTING AS A MODERATING VARIABLE - Siti Nurhaliza; Nela Safelia; Riski Hernando (Journal of Management Small and Medium Enterprises (SME's))
This study aims to explore how cash holding, quick ratio, and growth opportunities collectively and individually influence firm value, with Islamic Social Reporting serving as a moderating factor. The research involved a sample of 40 companies listed on the Jakarta Islamic Index 70 during the 2021-2022 period, selected using purposive sampling. SPSS 26 was utilized for data analysis, employing quantitative methods such as Moderated Regression Analysis. Findings revealed that individually, only cash holding significantly impacted firm value. However, collectively, cash holding, quick ratio, and growth opportunities did not demonstrate a significant influence on firm value. Additionally, Islamic Social Reporting did not moderate the relationships between cash holding, quick ratio, growth opportunities, and firm value.